2018
DOI: 10.1002/jso.25354
|View full text |Cite
|
Sign up to set email alerts
|

Overall survival of patients with colon cancer and a prolonged time to surgery

Abstract: Background Factors associated with the time to surgery (TTS) and survival in colon cancer (CC) have not been well studied. Our aim was to find if the TTS has changed in our institution over time and to determine if it influences the survival. Methods Retrospective cross‐section study of 266 CC analyzed between two periods, and according to the quartiles of TTS, we performed a survival analysis. Results The median age was 57 years; there was no predominance of sex, and about half of the patients were in stage I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…Colon adenocarcinoma (COAD) is the third most frequent cancer and the second main cause of cancer‐related death around the world and therefore has become a major public health problem (Cappell, 2008). Although great advances have been achieved on COAD treatment, the 5‑year survival rate of COAD patients still remains remarkably low (Lino‐Silva et al, 2019). As a result, it is urgent to study the molecular mechanism underlying the progression of COAD to develop novel and effective therapeutic strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Colon adenocarcinoma (COAD) is the third most frequent cancer and the second main cause of cancer‐related death around the world and therefore has become a major public health problem (Cappell, 2008). Although great advances have been achieved on COAD treatment, the 5‑year survival rate of COAD patients still remains remarkably low (Lino‐Silva et al, 2019). As a result, it is urgent to study the molecular mechanism underlying the progression of COAD to develop novel and effective therapeutic strategies.…”
Section: Introductionmentioning
confidence: 99%
“…In other studies, the definition of the time point used as diagnosis differed. One study used the date of the first investigation defining malignancy [ 24 ], while some studies used date of colonoscopy or first specialist consultation as the date of diagnosis [ 21 , 23 , 30 ]. Others used the date of confirmed pathological diagnosis as date of ‘diagnosis’ [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the remaining studies, median follow-up ranged from 2.4 to 5.4 years. Outcome in the majority of the studies (7 out of 10) was overall survival (OS) [ 21 24 , 26 , 27 , 30 ], two studies reported on relative survival (RS) [ 29 , 31 ], one study reported on all-cause death (ACD) and cancer-specific death (CSD) [ 25 ], and one study used cancer-specific mortality (CSM) [ 28 ]. Cancer-free survival (CFS) as an outcome was reported in four studies [ 24 , 30 , 31 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations